2014
DOI: 10.1509/jmr.13.0434
|View full text |Cite
|
Sign up to set email alerts
|

Surcharges plus Unhealthy Labels Reduce Demand for Unhealthy Menu Items

Abstract: Three laboratory experiments and a field experiment in a restaurant demonstrate that neither a price surcharge nor an unhealthy label is enough on its own to curtail the demand for unhealthy food. However, when the two are combined as an unhealthy label surcharge, they reduce demand for unhealthy food. The authors also show that the unhealthy label is as effective for women as the unhealthy label surcharge, whereas it backfires for men, who order more unhealthy food when there is an unhealthy label alone. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…Five studies were classified as cohort studies. Two studies were controlled before‐and‐after studies that reported outcomes in the same customers or at the food outlet level in the same food outlets at baseline and follow‐up , and four studies were controlled trials .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies were classified as cohort studies. Two studies were controlled before‐and‐after studies that reported outcomes in the same customers or at the food outlet level in the same food outlets at baseline and follow‐up , and four studies were controlled trials .…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the types of food outlets targeted, 18 studies focused on chain food outlets and 12 studies were set in other types of food outlet, including three studies in non‐chain food outlets ; one study each in takeaway food outlets ; a delicatessen‐style food outlet ; privately owned fast‐food‐style Mexican food outlets ; community food outlets that included both counter and table service ; Latino family‐owned food outlets ; licensed retail food outlets ; licensed hotels, clubs and nightclubs ; restaurants and cafes ; and small independent catering outlets . Most of the chain food outlets were fast food counter service, but other food outlet types included table service or takeaway only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of this research is to increase the effectiveness of the calorie information mandate using provincial norms to nudge consumers toward healthier decisions (Allcott ; Blumenthal‐Barby and Burroughs ; Payne et al ). We outline several actionable responses for issues faced by managers, practitioners, and policymakers seeking to enhance healthier consumption using social marketing techniques (see Shah et al ).…”
Section: Consumer‐based Strategic Implicationsmentioning
confidence: 99%